Investigation of Historical Hard Rubber Ornaments of Charles Goodyear. Issue 3 (20th December 2013) - Raue, M.; Wambach, M.; Glöggler, S.; Grefen, D.; Kaufmann, R.; Abetz, C.; Georgopanos, P.; Handge, U. A.; Mang, T.; Blümich, B.; Abetz, V.
<x xml:space="preserve">Abstract</x> Charles Goodyear discovered the vulcanization process of natural rubber in the middle of the 19th century. In this paper, original ornaments produced by Charles Goodyear are investigated. Additionally, for comparison, a sample is produced according to Goodyear's patent (US 3633) as reference. Contrary to expectation, it is found that Charles Goodyear did not prepare the ornaments using the formulation of his patent, thus he excluded the white lead. Due to this, another reference sample is produced like the other but without white lead. It is proven that by artificial aging, natural rubber samples can get properties similar to the 150 years old rubber sample. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>